2012
DOI: 10.1007/s12052-012-0429-7
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Attitudes and Literacy Survey (EALS): Development and Validation of a Short Form

Abstract: The Evolutionary Attitudes and Literacy Survey (EALS) is a multidimensional scale consisting of 16 lower- and 6 higher-order constructs developed to measure the wide array of factors that influence both an individual’s endorsement of and objection to evolutionary theory. Past research has demonstrated the validity and utility of the EALS (Hawley et al., Evol Educ Outreach 4:117–132, 2011); however, the 104-item long-form scale may be excessive for researchers and educators. The present study sought to reduce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 14 publications
2
31
0
Order By: Relevance
“…In other words, individuals who identified as more conservative were less likely to report engaging in rational thought, such as thinking in depth, or enjoy solving problems and intellectual challenges. In addition, the hypothesis that conservatism would be a negative predictor of relevance of evolution was supported, and congruent with previous research (Hawley et al, ; Short & Hawley, ). Individuals who identified as more conservative were less likely to view evolutionary theory relevant in areas including biology, the social sciences, and their everyday life.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In other words, individuals who identified as more conservative were less likely to report engaging in rational thought, such as thinking in depth, or enjoy solving problems and intellectual challenges. In addition, the hypothesis that conservatism would be a negative predictor of relevance of evolution was supported, and congruent with previous research (Hawley et al, ; Short & Hawley, ). Individuals who identified as more conservative were less likely to view evolutionary theory relevant in areas including biology, the social sciences, and their everyday life.…”
Section: Discussionsupporting
confidence: 85%
“…Attitudes central to one's self-concept, like political attitudes, are difficult to change (Pomerantz, Chaiken, & Tordesillas, 1995) and individuals tend to seek information which confirm their already held beliefs (Lord, Ross, & Lepper, 1979). For example, past research has found conservativism to be associated with less reported exposure to evolution, and lower knowledge and relevance of evolution (Hawley, Short, McCune, Osman, & Little, 2011;Short & Hawley, 2012). Researchers and practitioners interested in increasing individual's attitudes toward the relevance of evolution may not be very successful by trying to change individual political attitudes.…”
Section: Conservatism and Attitudes Toward Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The response to this question, therefore, is linked to whether the individual is considering simply Homo sapiens or the entire hominin lineage, thus potentially leading to an answer which indicates a belief in special creation rather than acceptance of human evolution. These faults appear to have minimal impact on our results, but they do suggest that a more extensive instrument of evolutionary acceptance, such as the EALS (Hawley 2011) or the EALS short from (Short and Hawley 2012) can useful in exploring the details of evolutionary acceptance. Whether these rather extensive questionnaires (the long version of the EALS has 104 questions; short version 62) can be effectively employed in a museum context remains to be seen.…”
Section: Study Limitationsmentioning
confidence: 71%
“…In their study, Short and Hawley (2012) have found the misconception that evolution would always create a more perfect creature, pointing to a misconception about an evolutionary chain extending from the simpler to the perfect. All these studies in the literature are consistent with the findings of this study.…”
Section: Necatibey Eğitim Fakültesi Elektronik Fen Ve Matematik Eğitimentioning
confidence: 99%